Optimised DC microgrid for future aircraft platforms - Mohamed, Mohamed (2022)
The aircraft industry's continued push towards the concept of a More Electric Aircraft (MEA), and All Electric Aircraft (AEA) to optimize its performance, decrease operating and maintenance costs, increase dispatch reliability, and reduce gas emissions. Particularly, the MEA concept aims to use electric power for all non-propulsive systems. Currently, the electrification trend is accelerating as aircraft Original Equipment Manufacturers (OEMs) engage with their suppliers to build new systems and install new power-dense electrically intensive architectures. This will lead to a significant challenge in the design of aircraft Electric Power systems (EPSs). The engineering community is currently researching various power system topologies. Among these topologies, single DC bus EPS architecture is considered one of the promising candidates for future MEA/AEA due to its simplicity. In this topology, the electrical power is provided from engine-driven generators to the single DC bus through Active Rectifiers (ARs).